1990
DOI: 10.1104/pp.92.4.1142
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation of Nodulation Mutants of Soybean as Affected by Nitrate

Abstract: It was previously reported that three soybean (Glycine max [L.] Merr.) nodulation mutants (NOD1-3, NOD2-4, and NOD3-7) were partially tolerant to nitrate when nitrate was supplied simultaneously with inoculation at the time of transplanting. The current study evaluated the effect of short-term nitrate treatment on nitrogenase activity (C2H2 reduction per plant and per nodule weight) and on relative abundance of ureides when nitrate application was delayed until plants were 3 weeks old and nodules were fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…3A, B). These results are also consistent with the findings reported in previous studies (Wu and Harper 1990). However, the response of ARA to nitrate cannot be simply explained by the higher nodule mass or number.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…3A, B). These results are also consistent with the findings reported in previous studies (Wu and Harper 1990). However, the response of ARA to nitrate cannot be simply explained by the higher nodule mass or number.…”
Section: Discussionsupporting
confidence: 83%
“…It was reported that the total nodule mass (dry weight) of NODl-3 was significantly higher than that of the parent even at a high level of nitrate supply (Gremaud and Harper 1989;Wu and Harper 1990). The results of the present study which included nitrate treatment (5 mM), contributed to new information indicating that the individual nodule growth estimated by the increase in the nodule diameter was also partially nitrate-tolerant in NODI-3 (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In the mutant type, the shoot-derived autoregulation signal would be either altered or absent, inducing a supernodulant and nitrate-tolerant (for nodulation) phenotype. In terms of nitrogen fixation, supernodulating mutants showed a low specific activity (C 2 H 2 reduction / nodule biomass), and this activity was reduced in the presence of nitrate in the same proportion as for the wild type parent (soybean: Hansen et al, 1990;Wu and Harper, 1990;pea: Jacobsen and Feenstra, 1984;com-mon bean: Buttery and Park, 1990). This last result was not always confirmed for soybean; a lower inhibition of specific activity was observed for the mutant type (Schuller et al, 1988).…”
mentioning
confidence: 99%